An estimation of the future adoption rate of autonomous trucks by freight organizations - Simpson, Jesse R.; Mishra, Sabyasachee; Talebian, Ahmadreza; Golias, Mihalis (My University, 2019)
This paper presents a model to estimate the future adoption of connected autonomous trucks (CATs) by freight transportation organizations. An accurate estimation of the market penetration rate of CATs is necessary to adequately prepare the infrastructure and legislation needed to support the technology. Building upon the theory of Diffusion of Innovations, we develop Bass models for various freight transportation innovations, including improved tractor and trailer aerodynamics, and anti-idling technologies for trucks. The proposed model accounts for heterogeneity between organizations by using a modified Bass model to vary parameters within a designated range for each of the potentially adopting organizations. The results of the paper are Bass models for existing freight organization innovation adoption and estimates of multiple scenarios of CAT adoption over time by freight organizations within the case study region of Shelby County, Tennessee and provide a foundation for organizational innovation adoption research. Our analyses suggest that the market penetration rate of CATs within 25 years varies from nearly universal adoption (i.e., more than 95%) to 20% or less depending on the rate at which autonomous technology improves over time, changes in public opinion on autonomous technology, and the addition of external influencing factors such as price and marketing.
Keywords: Connected autonomous trucks; Organizational adoption; Diffusion of innovations; Freight transportation; Market penetration predictions